Factors that hinder students to recognise and produce some classroom language expressions to talk with the teacher and classmates. - Gutiérrez Cevallos, Lizbeth Mariela (Machala : Universidad Técnica de Machala, 2015)
El objetivo general del presente trabajo es determinar los factores que impiden que los estudiantes reconozcan y produzcan algunas expresiones de lenguaje en el aula.
The overall objective of the present work is to determine the factors that hinder students to recognise and produce some classroom language expressions to talk in class.
Keywords: AULA; COMUNICACION; EXPRESION DE LENGUAJE; ESTUDIANTE